2005
DOI: 10.1099/vir.0.81145-0
|View full text |Cite
|
Sign up to set email alerts
|

The cotton rat provides a useful small-animal model for the study of influenza virus pathogenesis

Abstract: Influenza A virus continues to cause annual epidemics. The emergence of avian viruses in the human population poses a pandemic threat, and has highlighted the need for more effective influenza vaccines and antivirals. Development of such therapeutics would be enhanced by the use of a small-animal model that is permissive for replication of human influenza virus, and for which reagents are available to dissect the host response. A model is presented of nasal and pulmonary infection in adult inbred cotton rats (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
118
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 115 publications
(123 citation statements)
references
References 26 publications
5
118
0
Order By: Relevance
“…It has been shown that viral titers in nasal and lung tissues in cotton rats infected with human influenza viruses were proportional to the infectious dose, and this model replicated many respiratory features observed in humans (16). In addition, cotton rats have also been used in evaluation of cross-protective or heterosubtypic immunity (17,18), vaccines (19), and antiviral treatments against influenza (20).…”
mentioning
confidence: 66%
See 2 more Smart Citations
“…It has been shown that viral titers in nasal and lung tissues in cotton rats infected with human influenza viruses were proportional to the infectious dose, and this model replicated many respiratory features observed in humans (16). In addition, cotton rats have also been used in evaluation of cross-protective or heterosubtypic immunity (17,18), vaccines (19), and antiviral treatments against influenza (20).…”
mentioning
confidence: 66%
“…The cotton rat (Sigmodon hispidus) has been established as a model for influenza research as it is highly permissive for human influenza A and B viruses without prior adaptation (15,16). It has been shown that viral titers in nasal and lung tissues in cotton rats infected with human influenza viruses were proportional to the infectious dose, and this model replicated many respiratory features observed in humans (16).…”
mentioning
confidence: 87%
See 1 more Smart Citation
“…Hispid cotton rats (Sigmodon hispidus) provide a highly representative model for human infections since they are susceptible to a variety of human pathogens that do not require adaptation to infect and replicate (10)(11)(12)(13)(14). HRSV is a good example, as infection, pathology, and protection induced by candidate HRSV vaccines in cotton rats have already been explored and reflect the human situation (11,12,(15)(16)(17).…”
mentioning
confidence: 99%
“…Additionally, he worked closely with the RSV group and helped develop multiple small animal viral models utilizing the cotton rat, S hispidus. 28 …”
Section: Continuing To Lead the Waymentioning
confidence: 99%